Evaluation of the effect of fluconazole on the pharmacokinetics of cyclosporin A in healthy dogs after a single dose and at steady‐state. Issue 3 (1st September 2016) - Pieper, J. B.; Dirikolu, L.; Campbell, K. L.; Li, Z.; Mitchell, M. A.
Abstract : The aim of the study was to describe the effect of fluconazole on the pharmacokinetics of cyclosporin A in healthy dogs when investigated as a single dose and at steady‐state. Five healthy adult dogs were used in the study in a crossover design receiving either 5 mg/kg of cyclosporin A (CsA) alone or 5 mg/kg of fluconazole with 2.5 mg/kg of cyclosporin A (CsA/Flu) for 35 days. Pharmacokinetic curves were performed on day 1 and day 35 in addition to sampling trough and suspected peak concentrations (C2) twice weekly with LC/MS/MS. There was no statistically significant difference noted in any pharmacokinetic value (AUC0‐inf. [day 1, P = 0.225], AUCtau [day 35, P = 0.225], t ½ [day 1, P = 0.279; day 35, P = 0.686], and C max [day 1, P = 0.225; day 35, P = 0.225]) between the treatment groups by sampling day. There was a statistically significant increase in AUC (CsA P = 0.043; CsA/Flu P = 0.043) and t ½ (CsA P = 0.042, CsA/Flu P = 0.042) over time within each group. There were no significant differences in the C max (CsA P = 0.08; CsA/Flu P = 0.08) when comparing day 1 vs. day 35. Steady‐state cyclosporine concentrations were achieved by day 10 in both groups. Subjectively, individual variability was noted among the dogs and a much larger sample size would be beneficial in a future study.